Thermoplastic resin composition, molded article, metal foil laminate, bonding sheet, filament, and three-dimensional modeling material

By combining the crystalline thermoplastic polytamide resin and polyetherone resin, the heating plastic resin composition formed reduced the crystalline temperature during 3D printing, solved the problem of reducing adhesion and poor molding, and realized high resistance. Thermal and good thermal formability.

CN119384466APending Publication Date: 2025-01-28MITSUBISHI GAS CHEM CO INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380047700.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-13
Filing Date
2023-05-19
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The crystalline thermoplastic resin used in the prior art has reduced adhesion and poor molding due to the high crystallization temperature during the 3D printing process.

Method used

The thermoplastic resin composition containing a specific melting point difference is combined with the combination of crystalline thermoplastic polytamide resin with polyetherone resin, and the thermoplastic resin composition formed has a reduced crystalline temperature and the heat resistance and crystalline crystalline. Essence

Benefits of technology

It is achieved to maintain good thermal formability and adhesion during the 3D printing process, avoid the problem of decreased adhesion and poor molding, and at the same time, it has high heat resistance, suitable for applications such as connection and copper layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384466A_ABST
    Figure CN119384466A_ABST
Patent Text Reader

Abstract

A thermoplastic resin composition containing a crystalline thermoplastic polyimide resin (A) containing a repeating structural unit represented by formula (1) and a repeating structural unit represented by formula (2), and a polyetherketoneketone resin (B), the content ratio of the repeating structural unit of formula (1) to the total of the repeating structural unit of formula (1) and the repeating structural unit of formula (2) is 15-70 mol%, and the absolute value (TmA-TmB) of the difference between the melting point (TmA) of the component (A) and the melting point (TmB) of the component (B) is 0-40 DEG C. (In the formula, R1 represents a divalent group having 6-22 carbon atoms and containing at least one alicyclic hydrocarbon structure. And R2 represents a divalent chain aliphatic group having 5 to 16 carbon atoms. And each of X1 and X2 independently represents a tetravalent group having 6-22 carbon atoms and containing at least one aromatic ring. ). # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition, a molded body, a metal foil laminate, a joining sheet, a filament and a material for three-dimensional modeling. Background Art

[0002] Polyimide resin is a useful engineering plastic with high thermal stability, high strength, and high solvent resistance due to the rigidity, resonance stabilization, and strong chemical bonds of the molecular chain, and is used in a wide range of fields. In addition, polyimide resin with crystallinity can further improve its heat resistance, strength, and chemical resistance, and therefore, is expected to be used as a metal substitute, etc. However, polyimide resin has high heat resistance, but on the contrary, does not show thermoplasticity, and has a problem of low molding processability.

[0003] Therefore, in recent years, polyimide resins with thermoplasticity have been reported. In addition to the heat resistance originally possessed by polyimide resins, thermoplastic polyimide resins also have excellent molding processability. Therefore, thermoplastic polyimide resins can also be used for molded bodies used in harsh environments where nylon and polyester, which are general thermoplastic resins, cannot be applied.

[0004] For example, Patent Document 1 discloses a thermoplastic polyimide resin obtained by reacting a tetracarboxylic acid and / or a derivative thereof containing at least one aromatic ring, a diamine containing at least one alicyclic hydrocarbon structure, and a chain aliphatic diamine, and containing a predetermined repeating structural unit.

[0005] In the field of engineering plastics, there is also a known technique of compounding and alloying two or more thermoplastic resins for the purpose of improving physical properties, imparting functions suitable for the application, etc. Patent Document 2 discloses a thermoplastic polyimide resin containing a predetermined repeating unit, and also describes a scheme of using the polyimide resin and other resins as a polymer alloy.

[0006] Patent Document 3 discloses that a resin molded body containing a polyimide resin and a polyetherketone resin having a weight average molecular weight in a specific range and combining specific different polyimide structural units at a specific ratio has a high heat deformation temperature under a low load environment and excellent heat resistance.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2013 / 118704

[0010] Patent Document 2: International Publication No. 2016 / 147996

[0011] Patent Document 3: International Publication No. 2019 / 220969 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] The polyimide resins described in Patent Documents 1 to 3 are all crystalline thermoplastic resins.

[0014] However, in recent years, three-dimensional modeling technology using 3D printers and the like has been studied. General molding methods using 3D printers include the following: using a 3D printer, a molding material for a 3D printer containing a sinterable component and a binder component is stacked in a desired shape, and then fired to produce a molded body, which is a powder sintering stacking method; or a molding method in which a resin melted under heat is ejected from a nozzle and gradually stacked layer by layer, which is a thermal melt stacking method.

[0015] In the powder sintering stacking method, thermoplastic resins can be used as binder components. However, if a crystalline thermoplastic resin with a crystallization temperature that is too high is used, the stacked 3D printer molding materials will not be easy to adhere to each other, and shrinkage will occur due to the temperature difference in the stacking, thus, there is a concern that molding defects will occur.

[0016] An object of the present invention is to provide a thermoplastic resin composition comprising a crystalline thermoplastic resin, which maintains heat resistance and crystallinity and can lower the crystallization temperature than the crystalline thermoplastic resin.

[0017] Solutions for solving problems

[0018] The present inventors have found that a thermoplastic resin composition containing two specific types of crystalline thermoplastic resins having a melting point difference within a specific range can solve the above-mentioned problems.

[0019] That is, the present invention relates to the following.

[0020] [1] A thermoplastic resin composition comprising a crystalline thermoplastic polyimide resin (A) and a polyetherketoneketone resin (B), wherein the crystalline thermoplastic polyimide resin (A) comprises a repeating structural unit represented by the following formula (1) and a repeating structural unit represented by the following formula (2), wherein the content ratio of the repeating structural unit of the formula (1) to the total of the repeating structural unit of the formula (1) and the repeating structural unit of the formula (2) is 15 to 70 mol%.

[0021] Melting point Tm of the above-mentioned component (A) A The melting point Tm of the above-mentioned component (B) B The absolute value of the difference |Tm A -Tm B |0~40℃.

[0022]

[0023] (R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure. R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms. X1 and X2 are each independently a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.)

[0024] [2] The thermoplastic resin composition according to [1] above, wherein the melting point Tm of the component (A) is A and the melting point Tm of the aforementioned component (B) B The temperature ranges from 270 to 360°C.

[0025] [3] The thermoplastic resin composition according to [1] or [2], wherein the mass ratio of the component (A) to the component (B) in the thermoplastic resin composition is 1 / 99 to 80 / 20.

[0026] [4] The thermoplastic resin composition according to any one of [1] to [3] above, wherein the total content of the component (A) and the component (B) in the thermoplastic resin composition is 50% by mass or more.

[0027] [5] The thermoplastic resin composition according to any one of [1] to [4] above, wherein the heat of crystallization of the thermoplastic resin composition is 10 mJ / mg or more.

[0028] [6] The thermoplastic resin composition according to any one of [1] to [5] above, wherein the thermoplastic resin composition has a melting point Tm, and the difference between the melting point Tm and the crystallization temperature Tc of the thermoplastic resin composition (Tm-Tc) is 65°C or more.

[0029] [7] The thermoplastic resin composition according to [6] above, wherein the Tm-Tc is 80° C. or higher.

[0030] [8] The thermoplastic resin composition according to any one of [1] to [7] above, wherein the thermoplastic resin composition has a lamellar microphase separation structure.

[0031] [9] The thermoplastic resin composition according to any one of [1] to [8] above, further comprising a filler.

[0032]

[10] A molded article comprising the thermoplastic resin composition according to any one of [1] to [9] above.

[0033]

[11] A metal foil laminate comprising: a layer formed from the molded article according to

[10] ; and a layer formed from a metal foil.

[0034]

[12] A joining sheet comprising the thermoplastic resin composition according to any one of [1] to [9] above.

[0035]

[13] A filament comprising the thermoplastic resin composition according to any one of [1] to [9] above.

[0036]

[14] A three-dimensional modeling material comprising the thermoplastic resin composition according to any one of [1] to [9] above.

[0037] Effects of the Invention

[0038] The thermoplastic resin composition of the present invention has heat resistance and crystallinity, the rise of crystallization temperature is suppressed, the thermoformability is good, and it is not easy to produce a decrease in adhesion and shrinkage during three-dimensional modeling, so it is suitable as a molding material for a 3D printer, for example. In addition, the thermoplastic resin composition of the present invention has good adhesion to the adherend due to the effect of reducing the crystallization temperature, and has high heat resistance, so it is also suitable for application in metal foil laminates such as bonding sheets and copper-clad laminates. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram showing a method for preparing a sample (ultra-thin section) used for field emission scanning transmission electron microscopy (FE-STEM) observation.

[0040] Figure 2 This is a microscopic photograph of a cross section of the thermoplastic resin composition (pellet) of Example 3 cut in a direction perpendicular to the flow direction (MD) observed by FE-STEM.

[0041] Figure 3 This is a microscopic photograph of a cross section of the injection molded article obtained in Example 3 cut in a direction perpendicular to the flow direction (MD) observed by FE-STEM.

[0042] Figure 4 This is a schematic diagram for explaining a method for preparing a test piece used for evaluating the adhesion between films.

[0043] Figure 5 It is a schematic diagram for explaining the evaluation method of the adhesion between films.

[0044] Figure 6 This is a schematic diagram for explaining a method for preparing a test piece used for evaluating the adhesion between a film and a copper foil.

[0045] Figure 7 It is a schematic diagram for explaining the adhesion between a film and a copper foil and the evaluation method of the tensile adhesive strength. DETAILED DESCRIPTION

[0046] [Thermoplastic resin composition]

[0047] The thermoplastic resin composition of the present invention contains a crystalline thermoplastic polyimide resin (A) and a polyetherketoneketone resin (B), wherein the crystalline thermoplastic polyimide resin (A) contains a repeating structural unit represented by the following formula (1) and a repeating structural unit represented by the following formula (2), wherein the content ratio of the repeating structural unit of the formula (1) to the total of the repeating structural unit of the formula (1) and the repeating structural unit of the formula (2) is 15 to 70 mol%.

[0048] Melting point Tm of the above-mentioned component (A) A The melting point Tm of the above-mentioned component (B) B The absolute value of the difference |Tm A -Tm B |0~40℃.

[0049]

[0050] (R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure. R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms. X1 and X2 are each independently a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.)

[0051] According to the thermoplastic resin composition of the present invention, the component (A) and the component (B) which are crystalline thermoplastic resins can maintain heat resistance and crystallinity, and can lower the crystallization temperature than the crystalline thermoplastic resin. That is, the crystallization temperature of the thermoplastic resin composition becomes lower than the crystallization temperature of the component (A) alone or the component (B) alone as the raw material resin.

[0052] The reason why the above effects are obtained in the present invention is not clear, but it is found that: in the thermoplastic resin composition of the present invention and the molded article thereof, when |Tm A -Tm B When the components (A) and (B) are below the specific values, a lamellar microphase separation structure described later is formed by the intermolecular interaction between the components (A) and (B), and it is speculated that the crystallization temperature is reduced by the characteristic morphology. In addition, it is believed that sufficient heat resistance and crystallinity are maintained for practical use.

[0053] It should be noted that when a polyetheretherketone resin (PEEK) is used instead of the polyetherketoneketone resin as component (B), even if it is compounded with component (A), a lamellar microphase separation structure is not formed in the obtained thermoplastic resin composition and its molded body, and the effect of lowering the crystallization temperature is not manifested.

[0054] <Crystalline thermoplastic polyimide resin (A)>

[0055] The crystalline thermoplastic polyimide resin (A) used in the present invention (hereinafter, also referred to as "polyimide resin (A)") contains a repeating structural unit represented by the following formula (1) and a repeating structural unit represented by the following formula (2), and the content ratio of the repeating structural unit of the formula (1) relative to the total of the repeating structural unit of the formula (1) and the repeating structural unit of the formula (2) is 15 to 70 mol%.

[0056]

[0057] (R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure. R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms. X1 and X2 are each independently a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.)

[0058] The polyimide resin (A) used in the present invention is a crystalline thermoplastic resin, and its form is preferably powder or pellets. In this specification, "thermoplastic polyimide resin" refers to, for example, a polyimide resin having no glass transition temperature (Tg) formed by closing the imide ring after molding in the state of a polyimide precursor such as polyamic acid, or a polyimide resin that decomposes at a temperature below the glass transition temperature.

[0059] The repeating structural unit of formula (1) is described in detail below.

[0060] R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure. Here, the alicyclic hydrocarbon structure refers to a ring derived from an alicyclic hydrocarbon compound, and the alicyclic hydrocarbon compound may be saturated or unsaturated and may be monocyclic or polycyclic.

[0061] Examples of the alicyclic hydrocarbon structure include, but are not limited to, cycloalkane rings such as cyclohexane ring, cycloalkene rings such as cyclohexene, bicycloalkane rings such as norbornane ring, and bicycloalkene rings such as norbornene. Of these, cycloalkane rings are preferred, cycloalkane rings having 4 to 7 carbon atoms are more preferred, and cyclohexane rings are still more preferred.

[0062] R1 has 6 to 22 carbon atoms, preferably 8 to 17 carbon atoms.

[0063] R1 contains at least one alicyclic hydrocarbon structure, and preferably contains 1 to 3 alicyclic hydrocarbon structures.

[0064] R1 is preferably a divalent group represented by the following formula (R1-1) or (R1-2).

[0065]

[0066] (m11 and m 12 Each independently represents an integer of 0 to 2, and is preferably 0 or 1. 13 ~m 15 Each independently represents an integer from 0 to 2, preferably 0 or 1.)

[0067] R1 is particularly preferably a divalent group represented by the following formula (R1-3).

[0068]

[0069] In the divalent group represented by the above formula (R1-3), the positional relationship of the two methylene groups with respect to the cyclohexane ring may be cis or trans, and the ratio of cis to trans may be any value.

[0070] X1 is a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. The aromatic ring may be a monocyclic ring or a condensed ring, and examples thereof include a benzene ring, a naphthalene ring, an anthracene ring, and a tetracene ring, but are not limited thereto. Among these, a benzene ring and a naphthalene ring are preferred, and a benzene ring is more preferred.

[0071] X1 has 6 to 22 carbon atoms, preferably 6 to 18 carbon atoms.

[0072] X1 contains at least one aromatic ring, preferably 1 to 3 aromatic rings.

[0073] X1 is preferably a tetravalent group represented by any of the following formulae (X-1) to (X-4).

[0074]

[0075] (R 11 ~R 18 Each is independently an alkyl group having 1 to 4 carbon atoms. 11 ~p 13 Each independently represents an integer of 0 to 2, and is preferably 0. 14 、p 15 、p 16 and p 18 Each independently represents an integer of 0 to 3, and is preferably 0. 17 is an integer of 0 to 4, preferably 0. 11 ~L 13 Each is independently a single bond, an ether group, a carbonyl group or an alkylene group having 1 to 4 carbon atoms.)

[0076] It should be noted that X1 is a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. Therefore, R in formula (X-2) 12 , R 13 、p 12 and p 13The tetravalent group represented by the formula (X-2) is selected so that the number of carbon atoms in the group falls within the range of 10 to 22.

[0077] Similarly, L in formula (X-3) 11 , R 14 , R 15 、p 14 and p 15 The tetravalent group represented by formula (X-3) is selected so that the number of carbon atoms falls within the range of 12 to 22, and L in formula (X-4) 12 , L 13 , R 16 , R 17 , R 18 、p 16 、p 17 and p 18 The tetravalent group represented by the formula (X-4) is selected so that the number of carbon atoms in the group falls within the range of 18 to 22.

[0078] X1 is particularly preferably a tetravalent group represented by the following formula (X-5) or (X-6).

[0079]

[0080] Next, the repeating structural unit of formula (2) is described in detail below.

[0081] R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms, preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and still more preferably 8 to 10 carbon atoms. Here, the chain aliphatic group refers to a group derived from a chain aliphatic compound, and the chain aliphatic compound may be saturated or unsaturated, may be straight chain or branched, and may contain heteroatoms such as oxygen atoms.

[0082] R2 is preferably an alkylene group having 5 to 16 carbon atoms, more preferably an alkylene group having 6 to 14 carbon atoms, and still more preferably an alkylene group having 7 to 12 carbon atoms, and among these, an alkylene group having 8 to 10 carbon atoms is preferred. The alkylene group may be either a linear or branched chain, but a linear chain alkylene group is preferred.

[0083] R2 is preferably at least one selected from the group consisting of an octamethylene group and a decamethylene group, and is particularly preferably an octamethylene group.

[0084] In addition, another preferred embodiment of R2 includes a divalent chain aliphatic group having 5 to 16 carbon atoms including an ether group. The carbon number is preferably 6 to 14, more preferably 7 to 12, and even more preferably 8 to 10. Among them, a divalent group represented by the following formula (R2-1) or (R2-2) is preferred.

[0085]

[0086] (m 21 and m 22 Each independently represents an integer of 1 to 15, preferably 1 to 13, more preferably 1 to 11, and even more preferably 1 to 9. 23 ~m 25 Each independently represents an integer of 1 to 14, preferably 1 to 12, more preferably 1 to 10, and even more preferably 1 to 8.)

[0087] It should be noted that R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms (preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and even more preferably 8 to 10 carbon atoms). Therefore, m in formula (R2-1) is 21 and m 22 The divalent group represented by formula (R2-1) is selected so that the number of carbon atoms in the group falls within the range of 5 to 16 (preferably 6 to 14, more preferably 7 to 12, and even more preferably 8 to 10). 21 +m 22 It is 5 to 16 (preferably 6 to 14, more preferably 7 to 12, and even more preferably 8 to 10).

[0088] Similarly, m in formula (R2-2) 23 ~m 25 The divalent group represented by formula (R2-2) is selected so that the number of carbon atoms in the group falls within the range of 5 to 16 (preferably 6 to 14, more preferably 7 to 12, and even more preferably 8 to 10). 23 +m 24 +m 25 The carbon number is 5 to 16 (preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and even more preferably 8 to 10 carbon atoms).

[0089] X2 is defined similarly to X1 in formula (1), and preferred embodiments are also the same.

[0090] The content ratio of the repeating structural unit of formula (1) relative to the total of the repeating structural unit of formula (1) and the repeating structural unit of formula (2) is 15 to 70 mol%. When the content ratio of the repeating structural unit of formula (1) is within the above range, the polyimide resin (A) can be crystallized even in a general injection molding cycle, and the effect of lowering the crystallization temperature when compounded with the component (B) becomes easy to manifest.

[0091] The content ratio of the repeating structural units of formula (1) relative to the total of the repeating structural units of formula (1) and the repeating structural units of formula (2) is preferably 20 mol% or more, more preferably 25 mol% or more, further preferably 30 mol% or more, and further preferably 32 mol% or more from the viewpoint of molding processability, and is preferably 65 mol% or less, more preferably 60 mol% or less, further preferably 50 mol% or less, further preferably 40 mol% or less, further preferably less than 40 mol%, and further preferably 35 mol% or less from the viewpoint of maintaining high crystallinity.

[0092] The total content of the repeating structural units of the formula (1) and the repeating structural units of the formula (2) relative to the total repeating structural units constituting the polyimide resin (A) is preferably 50 to 100 mol%, more preferably 75 to 100 mol%, further preferably 80 to 100 mol%, and further preferably 85 to 100 mol%. It should be noted that the "total of all repeating structural units constituting the polyimide resin (A)" refers to the total of the structural units in the polyimide resin (A) when the structural unit containing one polyimide structure is regarded as one structural unit.

[0093] The polyimide resin (A) may further contain a repeating structural unit of the following formula (3). In this case, the content ratio of the repeating structural unit of formula (3) relative to the total of the repeating structural unit of formula (1) and the repeating structural unit of formula (2) is preferably 25 mol% or less, and from the viewpoint of maintaining crystallinity, it is preferably 20 mol% or less, and more preferably 15 mol% or less.

[0094] From the viewpoint of improving heat resistance, the content ratio is preferably 5 mol % or more, more preferably 10 mol % or more.

[0095]

[0096] (R3 is a divalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. X3 is a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.)

[0097] R3 is a divalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. The aromatic ring may be a monocyclic ring or a condensed ring, and examples thereof include a benzene ring, a naphthalene ring, an anthracene ring, and a tetracene ring, but are not limited thereto. Among these, a benzene ring and a naphthalene ring are preferred, and a benzene ring is more preferred.

[0098] R3 has 6 to 22 carbon atoms, preferably 6 to 18 carbon atoms.

[0099] R3 contains at least one aromatic ring, preferably 1 to 3 aromatic rings.

[0100] In addition, a monovalent or divalent electron-withdrawing group may be bonded to the aromatic ring. Examples of the monovalent electron-withdrawing group include a nitro group, a cyano group, a p-toluenesulfonyl group, a halogen group, a haloalkyl group, a phenyl group, an acyl group, and the like. Examples of the divalent electron-withdrawing group include fluorinated alkylene groups (e.g., -C(CF3)2-, -(CF2) p -(herein, p is an integer of 1 to 10))) and other halogenated alkylene groups, such as -CO-, -SO2-, -SO-, -CONH-, and -COO- can also be mentioned.

[0101] R3 is preferably a divalent group represented by the following formula (R3-1) or (R3-2).

[0102]

[0103] (m 31 and m 32 Each independently represents an integer of 0 to 2, and is preferably 0 or 1. 33 and m 34 Each independently represents an integer of 0 to 2, and is preferably 0 or 1. 21 , R 22 , and R 23 Each is independently an alkyl group having 1 to 4 carbon atoms, an alkenyl group having 2 to 4 carbon atoms, or an alkynyl group having 2 to 4 carbon atoms. 21 、p 22 and p 23 is an integer of 0 to 4, preferably 0. 21 is a single bond, an ether group, a carbonyl group, or an alkylene group having 1 to 4 carbon atoms.

[0104] It should be noted that R3 is a divalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. Therefore, m in formula (R3-1) 31 、m 32 , R 21 and p 21 The divalent group represented by the formula (R3-1) is selected so that the number of carbon atoms in the group falls within the range of 6 to 22.

[0105] Similarly, L in formula (R3-2) 21 、m 33 、m 34 , R 22 , R 23 、p 22 and p 23 The divalent group represented by the formula (R3-2) is selected so that the number of carbon atoms in the group falls within the range of 12 to 22.

[0106] X3 is defined similarly to X1 in formula (1), and preferred embodiments are also the same.

[0107] The polyimide resin (A) may further contain a repeating structural unit represented by the following formula (4).

[0108]

[0109] (R4 is -SO2- or -Si(R x )(R y )O- divalent group, R x and R y Each independently represents a chain aliphatic group having 1 to 3 carbon atoms or a phenyl group. X4 is a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.

[0110] X4 is defined similarly to X1 in formula (1), and preferred embodiments are also the same.

[0111] The terminal structure of the polyimide resin (A) is not particularly limited, and in addition to the terminal amino group and the terminal carboxyl group, the polyimide resin (A) may further have an aromatic ring-containing group, an aliphatic group, etc. Among them, the polyimide resin (A) preferably has a carbon 5-14 chain aliphatic group at the terminal.

[0112] The chain aliphatic group may be saturated or unsaturated, and may be linear or branched. When the polyimide resin (A) has the above-mentioned specific group at the terminal, a resin composition having excellent heat aging resistance can be obtained.

[0113] Examples of the saturated chain aliphatic group having 5 to 14 carbon atoms include n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, lauryl, n-tridecyl, n-tetradecyl, isopentyl, neopentyl, 2-methylpentyl, 2-methylhexyl, 2-ethylpentyl, 3-ethylpentyl, isooctyl, 2-ethylhexyl, 3-ethylhexyl, isononyl, 2-ethyloctyl, isodecyl, isododecyl, isotridecyl and isotetradecyl.

[0114] Examples of the unsaturated linear aliphatic group having 5 to 14 carbon atoms include 1-pentenyl, 2-pentenyl, 1-hexenyl, 2-hexenyl, 1-heptenyl, 2-heptenyl, 1-octenyl, 2-octenyl, nonenyl, decenyl, dodecenyl, tridecenyl and tetradecenyl.

[0115] Among them, the above-mentioned chain aliphatic group is preferably a saturated chain aliphatic group, and more preferably a saturated straight-chain aliphatic group. In addition, from the viewpoint of obtaining heat aging resistance, the above-mentioned chain aliphatic group preferably has a carbon number of 6 or more, more preferably a carbon number of 7 or more, further preferably a carbon number of 8 or more, preferably a carbon number of 12 or less, more preferably a carbon number of 10 or less, and further preferably a carbon number of 9 or less. The above-mentioned chain aliphatic group may be only one kind or two or more kinds.

[0116] The above-mentioned chain aliphatic group is particularly preferably at least one selected from the group consisting of n-octyl, isooctyl, 2-ethylhexyl, n-nonyl, isononyl, n-decyl and isodecyl, further preferably at least one selected from the group consisting of n-octyl, isooctyl, 2-ethylhexyl, n-nonyl and isononyl, and most preferably at least one selected from the group consisting of n-octyl, isooctyl and 2-ethylhexyl.

[0117] In addition, from the viewpoint of heat aging resistance, the polyimide resin (A) preferably has only a linear aliphatic group having 5 to 14 carbon atoms at the terminal in addition to a terminal amino group and a terminal carboxyl group. When a group other than the above is present at the terminal, the content thereof is preferably 10 mol% or less, more preferably 5 mol% or less, relative to the linear aliphatic group having 5 to 14 carbon atoms.

[0118] From the viewpoint of embodying excellent heat aging resistance, the content of the above-mentioned chain aliphatic group having 5 to 14 carbon atoms in the polyimide resin (A) is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, and further preferably 0.2 mol% or more, relative to the total of 100 mol% of all repeating structural units constituting the polyimide resin (A). In addition, in order to ensure sufficient molecular weight and obtain good mechanical properties, the content of the above-mentioned chain aliphatic group having 5 to 14 carbon atoms in the polyimide resin (A) is preferably 10 mol% or less, more preferably 6 mol% or less, and further preferably 3.5 mol% or less, relative to the total of 100 mol% of all repeating structural units constituting the polyimide resin (A).

[0119] The content of the linear aliphatic group having 5 to 14 carbon atoms in the polyimide resin (A) can be determined by depolymerizing the polyimide resin (A).

[0120] The polyimide resin (A) preferably has a melting point of 360° C. or less and a glass transition temperature of 150° C. or more. A From the viewpoint of heat resistance, it is preferably 270°C or more, more preferably 280°C or more, and further preferably 290°C or more. From the viewpoint of high molding processability, it is preferably 345°C or less, more preferably 340°C or less, and further preferably 335°C or less.

[0121] In addition, the glass transition temperature Tg of the polyimide resin (A) is preferably 160°C or higher, more preferably 170°C or higher from the viewpoint of heat resistance, and is preferably 250°C or lower, more preferably 230°C or lower, and further preferably 200°C or lower from the viewpoint of achieving high molding processability.

[0122] The crystallization temperature Tc of the polyimide resin (A) is preferably 200°C or higher, more preferably 220°C or higher, and further preferably 250°C or higher from the viewpoint of heat resistance, and is preferably 350°C or lower, more preferably 320°C or lower, and further preferably 300°C or lower from the viewpoint of molding processability.

[0123] For the polyimide resin (A), from the viewpoints of crystallinity, heat resistance, mechanical strength and chemical resistance, the heat of fusion Hm is preferably 5.0 mJ / mg or more, more preferably 10.0 mJ / mg or more, and further preferably 17.0 mJ / mg or more. The upper limit of the heat of fusion Hm is not particularly limited, but is usually 45.0 mJ / mg or less.

[0124] The heat of fusion Hm of the polyimide resin (A) refers to the heat of fusion peak near the melting point observed when the polyimide resin (A) is heated at a heating rate of 10°C / min to melt at a temperature above the melting point, then cooled at a cooling rate of 20°C / min, and then heated again at a heating rate of 10°C / min to melt, as measured by a differential scanning calorimeter.

[0125] In addition, for the polyimide resin (A), from the viewpoints of crystallinity, heat resistance, mechanical strength and chemical resistance, the heat of crystallization Hc is preferably 5.0 mJ / mg or more, more preferably 10.0 mJ / mg or more, and further preferably 17.0 mJ / mg or more. The upper limit of the heat of crystallization Hc is not particularly limited, but is usually 45.0 mJ / mg or less.

[0126] The heat of crystallization Hc of the polyimide resin (A) refers to the heat of a crystallization exothermic peak observed when the polyimide resin (A) is melted and then cooled at a temperature drop rate of 20° C. / min as measured by a differential scanning calorimeter.

[0127] Melting point Tm of polyimide resin (A) A , glass transition temperature Tg, crystallization temperature Tc, heat of fusion Hm and heat of crystallization Hc can be specifically measured by the methods described in Examples.

[0128] The logarithmic viscosity of a 0.5 mass % concentrated sulfuric acid solution of the polyimide resin (A) at 30°C is preferably in the range of 0.2 to 2.0 dL / g, more preferably in the range of 0.3 to 1.8 dL / g. If the logarithmic viscosity is 0.2 dL / g or more, sufficient mechanical strength is obtained when the obtained thermoplastic resin composition is made into a molded body, and if it is 2.0 dL / g or less, molding processability and operability become good. The logarithmic viscosity μ is obtained as follows: Using a Cannon-Fenske viscometer, the flow time of the concentrated sulfuric acid and the above-mentioned polyimide resin solution is measured at 30°C, and the logarithmic viscosity is obtained by the following formula.

[0129] μ=ln(ts / t0) / C

[0130] t0: time for concentrated sulfuric acid to flow

[0131] ts: Flow time of polyimide resin solution

[0132] C: 0.5 (g / dL)

[0133] The weight average molecular weight Mw of the polyimide resin (A) is preferably 10,000 to 150,000, more preferably 15,000 to 100,000, further preferably 20,000 to 80,000, further preferably 30,000 to 70,000, further preferably 35,000 to 65,000. When the weight average molecular weight Mw of the polyimide resin (A) is 10,000 or more, the mechanical strength of the obtained molded article becomes good, when it is 40,000 or more, the stability of the mechanical strength becomes good, and when it is 150,000 or less, the molding processability becomes good.

[0134] The weight average molecular weight Mw of the polyimide resin (A) can be measured by a gel filtration chromatography (GPC) method using polymethyl methacrylate (PMMA) as a standard sample.

[0135] (Method for producing polyimide resin (A))

[0136] The polyimide resin (A) can be produced by reacting a tetracarboxylic acid component containing a tetracarboxylic acid having at least one aromatic ring and / or a derivative thereof with a diamine component containing a diamine having at least one alicyclic hydrocarbon structure and a chain aliphatic diamine.

[0137] The tetracarboxylic acid containing at least one aromatic ring is preferably a compound obtained by directly bonding four carboxyl groups to the aromatic ring, and may also contain an alkyl group in the structure. In addition, the aforementioned tetracarboxylic acid is preferably one having 6 to 26 carbon atoms. As the aforementioned tetracarboxylic acid, pyromellitic acid, 2,3,5,6-toluenetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, etc. are preferred. Among these, pyromellitic acid is more preferred.

[0138] As the derivative of tetracarboxylic acid containing at least one aromatic ring, anhydride or alkyl ester of tetracarboxylic acid containing at least one aromatic ring can be mentioned. The above-mentioned tetracarboxylic acid derivative is preferably one having 6 to 38 carbon atoms. As the anhydride of tetracarboxylic acid, pyromellitic acid monoanhydride, pyromellitic acid dianhydride, 2,3,5,6-toluenetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and the like can be mentioned. Examples of the alkyl esters of tetracarboxylic acids include dimethyl pyromellitate, diethyl pyromellitate, dipropyl pyromellitate, diisopropyl pyromellitate, dimethyl 2,3,5,6-toluenetetracarboxylate, dimethyl 3,3',4,4'-diphenylsulfonetetracarboxylate, dimethyl 3,3',4,4'-benzophenonetetracarboxylate, dimethyl 3,3',4,4'-biphenyltetracarboxylate, and dimethyl 1,4,5,8-naphthalenetetracarboxylate. In the alkyl esters of the tetracarboxylic acids, the number of carbon atoms in the alkyl group is preferably 1 to 3.

[0139] As the tetracarboxylic acid and / or its derivative containing at least one aromatic ring, at least one compound selected from the above may be used alone or in combination of two or more compounds.

[0140] The carbon number of the diamine containing at least one alicyclic hydrocarbon structure is preferably 6 to 22, and examples thereof include 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, 4,4'-methylenebis(2-methylcyclohexylamine), carvonediamine, limonenediamine, isophoronediamine, norbornanediamine, bis(aminomethyl)tricyclo[5.2.1.0 2,6 ] decane, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 4,4'-diaminodicyclohexylpropane, etc. These compounds can be used alone or in combination with two or more compounds selected from these. Among these, 1,3-bis(aminomethyl)cyclohexane can be suitably used. It should be noted that the diamine containing an alicyclic hydrocarbon structure usually has structural isomers, but the ratio of cis-isomer / trans-isomer is not limited.

[0141] The chain aliphatic diamine may be straight chain or branched, and the carbon number is preferably 5 to 16, more preferably 6 to 14, and further preferably 7 to 12. In addition, the carbon number of the chain portion only needs to be 5 to 16, and an ether bond may be included therein. As the chain aliphatic diamine, for example, 1,5-pentamethylenediamine, 2-methylpentane-1,5-diamine, 3-methylpentane-1,5-diamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine, 1,13-tridecamethylenediamine, 1,14-tetradecamethylenediamine, 1,16-hexadecamethylenediamine, 2,2'-(ethylenedioxy)bis(ethylamine) and the like are preferred.

[0142] The chain aliphatic diamine may be used alone or in combination of two or more. Among these, chain aliphatic diamines having 8 to 10 carbon atoms are preferably used, and at least one selected from the group consisting of 1,8-octamethylenediamine and 1,10-decamethylenediamine is particularly preferably used.

[0143] When the polyimide resin (A) is produced, the molar ratio of the amount of the diamine containing at least one alicyclic hydrocarbon structure to the total amount of the diamine containing at least one alicyclic hydrocarbon structure and the chain aliphatic diamine is preferably 15 to 70 mol%. The molar amount is preferably 20 mol% or more, more preferably 25 mol% or more, further preferably 30 mol% or more, further preferably 32 mol% or more, and from the viewpoint of achieving high crystallinity, it is preferably 60 mol% or less, more preferably 50 mol% or less, further preferably less than 40 mol%, further preferably 35 mol% or less.

[0144] The diamine component may contain a diamine containing at least one aromatic ring. The diamine containing at least one aromatic ring preferably has 6 to 22 carbon atoms, and examples thereof include o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,2-diethynylphenylenediamine, 1,3-diethynylphenylenediamine, 1,4-diethynylphenylenediamine, 1,2-diaminobenzene, 1,3-diaminobenzene, 1,4-diaminobenzene, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, α,α'-bis(4-aminophenyl)1,4-diisopropylbenzene, α,α'-bis(3-aminophenyl)-1,4-diisopropylbenzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,6-diaminonaphthalene, and 1,5-diaminonaphthalene.

[0145] In the above, the molar ratio of the amount of the diamine containing at least one aromatic ring to the total amount of the diamine containing at least one alicyclic hydrocarbon structure and the chain aliphatic diamine is preferably 5 mol% or less, more preferably 20 mol% or less, and further preferably 15 mol% or less from the viewpoint of maintaining crystallinity. In addition, from the viewpoint of improving heat resistance, it is preferably 5 mol% or more, and more preferably 10 mol% or more.

[0146] From the viewpoint of reducing coloration of the polyimide resin (A), the molar ratio is preferably 12 mol% or less, more preferably 10 mol% or less, further preferably 5 mol% or less, and further preferably 0 mol%.

[0147] When producing the polyimide resin (A), the charging amount ratio of the above-mentioned tetracarboxylic acid component and the above-mentioned diamine component is preferably 0.9 to 1.1 mol of the diamine component relative to 1 mol of the tetracarboxylic acid component.

[0148] In addition, when manufacturing the polyimide resin (A), an end-capping agent may be mixed in addition to the aforementioned tetracarboxylic acid component and the aforementioned diamine component. As the end-capping agent, at least one selected from the group consisting of monoamines and dicarboxylic acids is preferred. The amount of the end-capping agent used is an amount that can introduce a desired amount of terminal groups into the polyimide resin (A), preferably 0.0001 to 0.1 mol, more preferably 0.001 to 0.06 mol, and further preferably 0.002 to 0.035 mol relative to 1 mol of the aforementioned tetracarboxylic acid and / or its derivative.

[0149] Among them, as the end-capping agent, a monoamine end-capping agent is preferred. From the viewpoint of introducing the aforementioned chain aliphatic group having 5 to 14 carbon atoms at the end of the polyimide resin (A) to improve heat aging resistance, a monoamine having a chain aliphatic group having 5 to 14 carbon atoms is more preferred, and a monoamine having a saturated straight-chain aliphatic group having 5 to 14 carbon atoms is further preferred.

[0150] The blocking agent is particularly preferably at least one selected from the group consisting of n-octylamine, isooctylamine, 2-ethylhexylamine, n-nonylamine, isononylamine, n-decylamine and isodecylamine, further preferably at least one selected from the group consisting of n-octylamine, isooctylamine, 2-ethylhexylamine, n-nonylamine and isononylamine, and most preferably at least one selected from the group consisting of n-octylamine, isooctylamine and 2-ethylhexylamine.

[0151] As a polymerization method for producing the polyimide resin (A), a known polymerization method can be applied, and the method described in International Publication No. 2016 / 147996 can be used.

[0152] <Polyetherketoneketone resin (B)>

[0153] The thermoplastic resin composition of the present invention contains a specific crystalline thermoplastic polyimide resin (A) and a polyetherketoneketone resin (B).

[0154] Preferred examples of the polyetherketoneketone resin (B) include resins represented by the following structural formula (I).

[0155]

[0156] (In the formula, p and q are each independently a number indicating the number of structural units.)

[0157] The resin represented by the above structural formula (I) is produced using diphenyl ether, terephthaloyl chloride, and isophthaloyl chloride.

[0158] From the viewpoint of ensuring crystallinity and obtaining a sufficient effect of lowering the crystallization temperature when compounded with component (A), in the resin represented by the aforementioned structural formula (I), the molar ratio of the structural unit derived from terephthaloyl chloride to the structural unit derived from isophthaloyl chloride (hereinafter also referred to as "T / I ratio") is preferably 50 / 50 to 99 / 1, more preferably 50 / 50 to 90 / 10, further preferably 60 / 40 to 80 / 20, further preferably 60 / 40 to 75 / 25, further preferably 65 / 35 to 75 / 25.

[0159] Melting point Tm of polyetherketoneketone resin (B) B From the viewpoint of heat resistance, it is preferably 270°C or more, more preferably 280°C or more, and further preferably 290°C or more. From the viewpoint of high molding processability, it is preferably 360°C or less, more preferably 345°C or less, further preferably 340°C or less, and further preferably 335°C or less.

[0160] The glass transition temperature of the polyetherketoneketone resin (B) is 140°C or higher, more preferably 150°C or higher from the viewpoint of heat resistance, and is preferably 200°C or lower, more preferably 180°C or lower from the viewpoint of achieving high molding processability.

[0161] Melting point Tm of polyetherketoneketone resin (B) B The glass transition temperature and the glass transition temperature can be measured using a differential scanning calorimeter in the same manner as in the case of the component (A).

[0162] As the polyetherketoneketone resin (B), commercially available products such as polyetherketoneketone resin (PEKK) 6000 series, 7000 series, and 8000 series manufactured by ARKEMA may be used.

[0163] Here, from the viewpoint of obtaining the effect of lowering the crystallization temperature, the melting point Tm of the component (A) used in the thermoplastic resin composition is preferablyA Melting point Tm of component (B) B The absolute value of the difference |Tm A -Tm B | is 0 to 40°C, preferably 0 to 30°C, more preferably 0 to 20°C, further preferably 0 to 15°C.

[0164] |Tm A- Tm B |When it is not 0, Tm A With Tm B Any of can be a high temperature.

[0165] In addition, from the viewpoint of improving crystallinity and heat resistance and ensuring appropriate crystallinity, the melting point Tm of the component (A) used in the thermoplastic resin composition is preferably 0.0547 W / cm2. A and the melting point Tm of component (B) B The temperature is preferably in the range of 270 to 360°C, more preferably in the range of 280 to 350°C, and still more preferably in the range of 290 to 345°C.

[0166] From the viewpoint of improving the effect of lowering the crystallization temperature and ensuring appropriate crystallinity, the mass ratio of component (A) to component (B) in the thermoplastic resin composition is preferably 1 / 99 to 80 / 20, more preferably 5 / 95 to 70 / 30, further preferably 10 / 90 to 70 / 30, and still further preferably 15 / 85 to 70 / 30.

[0167] <Filling materials>

[0168] The thermoplastic resin composition of the present invention may further contain a filler according to desired properties.

[0169] The shape of the filler is not particularly limited, and any filler in the form of granules, plates, or fibers may be used. The particle size of the granules or plates may be appropriately selected according to the application of the thermoplastic resin composition, but from the viewpoint of maintaining the molding processability of the thermoplastic resin composition and improving the mechanical strength of the obtained molded body, the average particle size is preferably 0.1 to 200 μm, more preferably 0.5 to 100 μm.

[0170] From the viewpoint of heat resistance, the filler is preferably an inorganic filler. As granular or plate-like inorganic fillers, silicon dioxide, aluminum oxide, kaolinite, wollastonite, mica, talc, clay, sericite, magnesium carbonate, barium carbonate, magnesium sulfate, barium sulfate, calcium oxide, silicon carbide, antimony trisulfide, tin sulfide, copper sulfide, iron sulfide, bismuth sulfide, zinc sulfide, glass, etc. can be cited. It should be noted that the above-mentioned glass can be glass powder, glass flakes, and glass beads.

[0171] Examples of the fibrous inorganic filler include glass fiber, carbon fiber, metal fiber, graphite fiber, silica fiber, silica / alumina fiber, alumina fiber, zirconia fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate whisker, aluminum borate whisker, magnesium whisker, silicon whisker, and the like.

[0172] It should be noted that these inorganic fillers may be surface treated.

[0173] When the thermoplastic resin composition contains a filler, the content of the filler in the thermoplastic resin composition varies depending on the desired performance, but is preferably 0.05 to 70 mass %, more preferably 0.1 to 50 mass %, and even more preferably 1 to 30 mass %.

[0174] <Additives>

[0175] The thermoplastic resin composition of the present invention may further contain additives such as a matting agent, a plasticizer, an antistatic agent, an anti-coloring agent, an anti-gelling agent, a colorant, a slip improver, an antioxidant, an ultraviolet light blocking agent, a conductive agent, and a resin modifier, in addition to the above, as required.

[0176] When the above-mentioned additives are used, there is no particular limitation on the amount thereof blended. From the viewpoint of maintaining the physical properties derived from the polyimide resin (A) and the polyetherketoneketone resin (B) and expressing the effects of the additives, the amount thereof is usually 50% by mass or less, preferably 0.0001 to 30% by mass, more preferably 0.001 to 15% by mass, and still more preferably 0.01 to 10% by mass in the thermoplastic resin composition.

[0177] In addition, the thermoplastic resin composition of the present invention may contain other resins other than the polyimide resin (A) and the polyetherketoneketone resin (B) within the range that does not hinder the properties thereof. As such other resins, preferably thermoplastic resins with high heat resistance are used, for example, polyamide resins, polyester resins, polyimide resins other than the polyimide resin (A), polycarbonate resins, polyetherimide resins, polyamideimide resins, polyphenylene etherimide resins, polyphenylene sulfide resins, polysulfone resins, polyethersulfone resins, polyarylate resins, liquid crystal polymers, polyetheretherketone resins, polyetherketone resins, polyetheretherketoneketone resins, polybenzimidazole resins, etc. may be mentioned.

[0178] Among them, from the viewpoint of sufficiently obtaining the effect of lowering the crystallization temperature, the total content of the component (A) and the component (B) in the thermoplastic resin composition of the present invention is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 50% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more and 100% by mass or less.

[0179] The thermoplastic resin composition of the present invention may take any form, but is preferably in the form of pellets.

[0180] When the thermoplastic resin composition of the present invention is in the form of pellets, for example, the polyimide resin (A), the polyetherketoneketone resin (B), and various optional components as required are added and dry-mixed, or the polyetherketoneketone resin (B) and optional components are separately fed into the extruder from a different point from the polyimide resin (A), and then melt-kneaded in the extruder to extrude a strand, and the strand is cut to form a pellet.

[0181] From the viewpoint of forming a pellet form, the thermoplastic resin composition of the present invention preferably does not contain a solvent. Specifically, the content of the solvent in the thermoplastic resin composition is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.1% by mass or less.

[0182] From the viewpoint of ensuring sufficient crystallinity, the thermoplastic resin composition preferably has a crystallization heat Hc of 10 mJ / mg or more, more preferably 15 mJ / mg or more, and even more preferably 17 mJ / mg or more. The upper limit of the crystallization heat Hc of the thermoplastic resin composition is not particularly limited, but is usually 45 mJ / mg or less.

[0183] In addition, from the viewpoint of ensuring sufficient crystallinity and improving thermoformability, the thermoplastic resin composition preferably has a melting point Tm, and the difference (Tm-Tc) between the melting point Tm and the crystallization temperature Tc of the thermoplastic resin composition is 65° C. or more. (Tm-Tc) is more preferably 70° C. or more, further preferably 80° C. or more, and further preferably 95° C. or more. The upper limit of (Tm-Tc) is not particularly limited, but is usually 150° C. or less.

[0184] The melting point Tm of the thermoplastic resin composition is preferably 270° C. or higher, more preferably 280° C. or higher, further preferably 290° C. or higher, and further preferably 320° C. or higher from the viewpoint of heat resistance, and is preferably 360° C. or lower, more preferably 345° C. or lower, further preferably 340° C. or lower, and further preferably 335° C. or lower from the viewpoint of achieving high thermoformability.

[0185] The crystallization heat Hc, melting point and crystallization temperature of the thermoplastic resin composition can be measured in the same manner as described above. In addition, when multiple peaks of crystallization temperature Tc are observed, it is preferred that Tm and the peak Tc located on the lowest temperature side are MIN The difference (Tm-Tc MIN ) becomes the above range.

[0186] For the Tc of the thermoplastic resin composition MINFrom the viewpoint of ensuring sufficient crystallinity, it is preferably above 190°C, more preferably above 200°C, and further preferably above 220°C. From the viewpoint of exhibiting sufficient adhesion, it is preferably below 300°C, more preferably below 270°C, and further preferably below 255°C.

[0187] [Molding body]

[0188] The present invention provides a molded article comprising the aforementioned thermoplastic resin composition.

[0189] The thermoplastic resin composition of the present invention has thermoplasticity, and therefore, the molded article of the present invention can be easily manufactured by performing thermoforming. As thermoforming methods, injection molding, extrusion molding, inflation molding, blow molding, hot press molding, vacuum molding, pressure molding, laser molding, welding, fusion, 3D printer molding, etc. can be cited, and any method can be used as long as it is a molding method that undergoes a heat melting process.

[0190] Thermoforming is preferred because it can be performed without setting the molding temperature to a high temperature, for example, exceeding 400°C. In the case of injection molding, it can be performed without setting the molding temperature and the mold temperature during molding to high temperatures, so it is preferred. For example, in injection molding, molding can be performed by setting the molding temperature to preferably 400°C or less, more preferably 360°C or less, and the mold temperature to preferably 260°C or less, more preferably 220°C or less.

[0191] As a method for producing a molded body, for example, after drying the pellets produced by the above method, the pellets are introduced into various molding machines and thermoformed preferably at 290 to 360° C., a molded body having a desired shape can be produced.

[0192] The shape of the molded article of the present invention is not particularly limited, and examples thereof include sheets, films, tows, filaments, etc. These may be intermediate members of industrial products or final products.

[0193] For example, if a 3D printer molding method is used in the production of a molded body, a filament-shaped molded body can be easily produced. That is, according to the present invention, a filament comprising the above-mentioned thermoplastic resin composition can be provided.

[0194] The shape of the filament is not particularly limited, but from the viewpoint of production by 3D printer molding, the filament diameter is preferably 10 mm or less, more preferably 5 mm or less, further preferably 3.5 mm or less, and preferably 0.1 mm or more.

[0195] The molded article of the present invention may be a fiber-reinforced composite material obtained by impregnating continuous fibers such as carbon fibers and glass fibers with the thermoplastic resin composition.

[0196] The thermoplastic resin composition and molded article of the present invention preferably have a lamellar microphase separation structure. "Lamellar microphase separation structure" refers to a substantially lamellar or fibrous microphase separation structure, which can be identified by observing the surface or cross section of the thermoplastic resin composition or molded article using a scanning transmission electron microscope (STEM). The aspect ratio of the substantially lamellar or fibrous phase separation structure in the lamellar microphase separation structure is preferably 4 or more, more preferably 5 or more, and usually 200 or less.

[0197] The microphase separation structure of the thermoplastic resin composition or the molded product can be observed by the method described in Examples.

[0198] <Applications>

[0199] The thermoplastic resin composition of the present invention has heat resistance and crystallinity, the rise of crystallization temperature is suppressed, the thermoformability is good, and it is not easy to produce adhesiveness reduction and shrinkage during three-dimensional modeling. Therefore, it is suitable as a molding material for 3D printers, for example. In addition, the thermoplastic resin composition of the present invention embodies good adhesion to the adherend according to the reduction effect of crystallization temperature, and the heat resistance is also high. Therefore, it is also suitable for the application in metal foil laminates such as bonding sheets and copper-clad laminates.

[0200] Therefore, the present invention can provide a three-dimensional modeling material and a joining sheet comprising the thermoplastic resin composition.

[0201] The present invention can also provide a metal foil laminate having a layer formed of a molded product containing the thermoplastic resin composition and a layer formed of a metal foil.

[0202] As the metal foil laminate, a copper-clad laminate can be mainly mentioned, and the copper-clad laminate has only to have a layer formed of a film-shaped molded body containing the aforementioned thermoplastic resin composition (hereinafter, also referred to as "resin film layer") and at least one copper foil layer. For example, a laminate having a structure in which copper foil is laminated on at least one surface, preferably both surfaces, of a resin film containing the aforementioned thermoplastic resin composition can be mentioned.

[0203] The resin film used in the manufacture of the copper-clad laminate can be manufactured by the same method as the manufacturing method of the aforementioned molded body. From the viewpoint of ensuring the strength of the copper-clad laminate and improving the adhesion between the resin film layer and the copper foil layer, the thickness of the resin film and the resin film layer in the copper-clad laminate is preferably 5 to 500 μm, more preferably 10 to 300 μm, and further preferably 12.5 to 200 μm.

[0204] The copper foil used in the manufacture of the copper-clad laminate is not particularly limited, and commercially available rolled copper foil, electrolytic copper foil, etc. can be used, but from the viewpoint of flexibility, rolled copper foil is preferred. From the viewpoint of ensuring sufficient conductivity and improving adhesion to the resin film layer, the thickness of the copper foil layer and the copper foil used in its formation is preferably 2 to 50 μm, more preferably 3 to 30 μm, and further preferably 5 to 20 μm. This thickness is the thickness of each copper foil layer or each copper foil.

[0205] In addition, the surface roughness of the copper foil used in the manufacture of the copper-clad laminate is not particularly limited. The surface roughness of the copper foil is directly related to the electrical properties of the laminate itself obtained after the resin film is laminated. Generally, the lower the roughness, the better the laminate with excellent dielectric properties. Therefore, the value of the maximum height roughness Rz of the copper foil surface is preferably 0.1 to 1 μm, more preferably in the range of 0.2 to 0.8 μm. The maximum height roughness Rz of the copper foil surface can be measured, for example, using a surface roughness meter.

[0206] From the viewpoint of improving the strength and conductivity of the copper-clad laminate, the thickness of the copper-clad laminate is preferably 15 to 600 μm, more preferably 25 to 500 μm, and further preferably 50 to 300 μm. It should be noted that the copper-clad laminate may have any layer other than the resin film layer and the copper foil layer as long as the effect of the present invention is not impaired.

[0207] The method for manufacturing the copper-clad laminate is not particularly limited, and a known method can be used. For example, the following method can be cited: overlapping the resin film and the copper foil, and then laminating them under heating and pressurizing conditions. The resin film contains a thermoplastic polyimide resin (A), so it can be pressed and bonded to the copper foil in a state where the surface is hot-melted.

[0208] As a device used in the manufacture of copper-clad laminates, any device that can bond resin film to copper foil under heating and pressurizing conditions can be used, for example, a roller laminator, a flat laminator, a vacuum pressurizing device, a double-belt pressurizing device, etc. can be cited. Among these, from the perspective of the productivity of the copper-clad laminate and the perspective of obtaining a copper-clad laminate with good appearance, it is preferred to use a vacuum pressurizing device or a double-belt pressurizing device. The double-belt pressurizing device refers to a device having an endless belt with a pair of upper and lower configurations, and continuously conveying materials (resin film and copper foil) forming the film shape of each layer between the belts, and using the endless belt, the aforementioned materials are heated and pressurized by a heating and pressing mechanism to form a laminate.

[0209] Examples of the double-belt pressurizing device include a device described in Japanese Patent Application Laid-Open No. 2010-221694 and a double-belt pressurizing device manufactured by DYMCO Corporation.

[0210] The heating temperature when manufacturing the copper-clad laminate by the above method is not particularly limited as long as it is a temperature at which the resin film can be softened or melted. From the perspective of reducing the burden on the device and manufacturing, it is preferably in the range of 250 to 400°C, and more preferably in the range of 280 to 350°C. In addition, the pressurization conditions when manufacturing the copper-clad laminate are as follows: from the perspective of improving the adhesion between the resin film and the copper foil and reducing the burden on the device and manufacturing, the pressure is preferably 0.1 to 20 MPa, more preferably 0.15 to 15 MPa, and further preferably 0.2 to 12 MPa. In addition, from the perspective of improving production efficiency, the pressurization time is preferably in the range of 1 to 600 seconds, more preferably 5 to 400 seconds, and further preferably 10 to 300 seconds.

[0211] It should be noted that the aforementioned resin film is characterized in that it can be heat-fused, but in the manufacture of the copper-clad laminate, an adhesive can also be used to make the resin film and the copper foil adhere. As an adhesive, a varnish-like adhesive, a sheet-like adhesive, a powdery adhesive, etc. can be arbitrarily selected. On the other hand, from the viewpoint of ensuring low dielectric properties, as an adhesive, it is also suitable to have a low dielectric property person. As an adhesive of low dielectric properties, for example, the polyimide adhesive "PIAD" series of Arakawa Chemical Industries, Ltd. can be enumerated.

[0212] Other uses of the thermoplastic resin composition or molded article of the present invention include transportation equipment (automobiles, airplanes, etc.), industrial equipment, electrical and electronic components, semiconductor / liquid crystal manufacturing equipment parts (wafer carriers, IC trays, conveyor rollers, etc.), food / beverage manufacturing equipment parts, medical equipment parts (casings of various instruments, sterilizing equipment, disinfecting equipment, biological materials, HPLC columns, filters, infusion pump gears, equipment handles, etc.), aircraft parts (clips, bracket fasteners, structural parts, compartment retainers, ventilation grilles, etc.), satellite parts, insulating films, belt films for copy machines, switches, connectors, motor parts, bearings, seals, gears, compressor rings, valves, pipes, ABS brake systems, transmission parts, thrust washers, seal rings, piston parts, spindle nuts, slot liners (insulating paper), biological materials (catheter tubes, artificial hip joints, artificial tooth roots, crowns, bridges, removable bases, etc.), speaker diaphragms, monofilaments, coating materials (wire covering materials, etc.).

[0213] Example

[0214] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited thereto. In addition, various measurements and evaluations in each of the production examples and Examples were performed as follows.

[0215] <Infrared spectroscopy analysis (IR measurement)>

[0216] The IR measurement of the polyimide resin was performed using "JIR-WINSPEC50" manufactured by JEOL Ltd.

[0217] <Logarithmic viscosity μ>

[0218] After drying the polyimide resin at 190 to 200° C. for 2 hours, a polyimide resin solution prepared by dissolving 0.100 g of the polyimide resin in 20 mL of concentrated sulfuric acid (96%, manufactured by Kanto Chemical Co., Ltd.) was used as a measurement sample and measured at 30° C. using a Cannon-Fenske viscometer. The logarithmic viscosity μ was determined according to the following formula.

[0219] μ=ln[(ts / t0) / C]

[0220] t0: time for concentrated sulfuric acid to flow

[0221] ts: Flow time of polyimide resin solution

[0222] C: 0.5 g / dL

[0223] <Melting point, glass transition temperature, crystallization temperature, heat of fusion, heat of crystallization>

[0224] The melting point Tm, glass transition temperature Tg, crystallization temperature Tc, heat of fusion Hm and heat of crystallization Hc of the thermoplastic resin alone or the thermoplastic resin composition obtained in each example were measured using a differential scanning calorimeter ("DSC-25" manufactured by TA Instruments). In the measurement of the crystallization temperature Tc, for polyimide resins, resin powders were used as measurement samples, and for other crystalline thermoplastic resins and crystalline thermoplastic resin compositions, pellets were used as measurement samples.

[0225] In a nitrogen atmosphere, the measurement sample was subjected to a thermal history under the following conditions: first heating (heating rate 10°C / min), followed by cooling (temperature reduction rate 20°C / min), and then second heating (heating rate 10°C / min).

[0226] The melting point Tm is determined by reading the peak value of the endothermic peak observed during the second heating. The glass transition temperature Tg is determined by reading the value observed during the second heating. The crystallization temperature Tc is determined by reading the peak value of the exothermic peak observed during cooling. It should be noted that, with respect to Tm, Tg and Tc, when multiple peaks are observed, the peak value of each peak is read.

[0227] The heat of fusion Hm (mJ / mg) is calculated as follows: for the measurement sample, after heating at a temperature of 10°C / min to a temperature above the melting point and melting, cooling at a temperature drop rate of 20°C / min, melting again at a temperature rise rate of 10°C / min, and calculating from the area of ​​the heat of fusion peak (endothermic peak) near the melting point observed at this time. In addition, the heat of crystallization Hc (mJ / mg) is calculated as follows: for the measurement sample, after heating at a temperature rise rate of 10°C / min to a temperature above the melting point and melting, cooling at a temperature drop rate of 20°C / min, and calculating from the area of ​​the exothermic peak of crystallization observed at this time.

[0228] <Half crystallization time>

[0229] The half crystallization time of the polyimide resin is measured using a differential scanning calorimeter ("DSC-6220" manufactured by SII NanoTechnology Inc.).

[0230] In a nitrogen atmosphere, the polyimide resin was completely melted by keeping the temperature at 420°C for 10 minutes, and then a rapid cooling operation was performed at a cooling rate of 70°C / min. The time taken from the appearance of the crystallization peak observed at this time to the peak top was calculated. It should be noted that in Table 1, the case where the half-crystallization time is less than 20 seconds is recorded as "<20".

[0231] <Weight average molecular weight>

[0232] The weight average molecular weight (Mw) of the polyimide resin was measured using a gel filtration chromatography (GPC) measuring apparatus "Shode XGPC-101" manufactured by Showa Denko K.K. under the following conditions.

[0233] Column: ShodeXHFIP-806M

[0234] Mobile phase solvent: Hexafluoroisopropanol (HFIP) containing 2 mM sodium trifluoroacetate

[0235] Column temperature: 40°C

[0236] Mobile phase flow rate: 1.0 mL / min

[0237] Sample concentration: about 0.1 mass%

[0238] Detector: IR detector

[0239] Injection volume: 100μm

[0240] Standard curve: Standard PMMA

[0241] <Heat Deformation Temperature (HDT)>

[0242] Using the thermoplastic resin used in each example alone or the thermoplastic resin composition obtained in each example, a molded article of 80 mm×10 mm×4 mm in thickness was produced according to the method described below and used for measurement.

[0243] The measurement was conducted in accordance with JIS K7191-1, 2: 2015, and the test was performed under flat winding. Specifically, the heat deformation temperature was measured using a HDT tester "Auto-HDT3D-2" (manufactured by Toyo Seiki Seisaku-sho, Ltd.) under the conditions of a support distance of 64 mm, a load of 1.80 MPa, and a heating rate of 120°C / hour.

[0244] <Tm-Tc MIN >

[0245] The difference between the melting point Tm and the crystallization temperature Tc measured by the above method is calculated. It should be noted that when two or more crystallization temperature Tc peaks are confirmed, the peak value (Tc MIN ) are shown in Table 2.

[0246] Production Example 1 (Production of Polyimide Resin 1)

[0247] In a 2L separable flask equipped with a Dean-Stark trap, a Liebig condenser, a thermocouple, and four paddles, 500 g of 2-(2-methoxyethoxy)ethanol (manufactured by Nippon Emulsifier Co., Ltd.) and 218.12 g (1.00 mol) of pyromellitic dianhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.) were introduced, and nitrogen was flowed, followed by stirring at 150 rpm to obtain a uniform suspension solution. On the other hand, 49.79 g (0.35 mol) of 1,3-bis(aminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., cis / trans ratio = 7 / 3) and 93.77 g (0.65 mol) of 1,8-octamethylenediamine (manufactured by Kanto Chemical Co., Ltd.) were dissolved in 250 g of 2-(2-methoxyethoxy)ethanol in a 500 mL beaker to prepare a mixed diamine solution. The mixed diamine solution was slowly added using a plunger pump. Heat was released by the addition, but the internal temperature was adjusted to fall within the range of 40 to 80°C. A nitrogen flow state was formed during the addition of the mixed diamine solution, and the stirring blade speed was set to 250 rpm. After the addition was completed, 130 g of 2-(2-methoxyethoxy)ethanol and 1.284 g (0.010 mol) of n-octylamine (manufactured by Kanto Chemical Co., Ltd.) as an end-capping agent were added and further stirred. At this stage, a light yellow polyamic acid solution was obtained. Next, after the stirring speed was set to 200 rpm, the polyamic acid solution in the 2L detachable flask was heated to 190°C. During the gradual heating process, the precipitation of polyimide resin powder and dehydration accompanied by imidization were confirmed when the liquid temperature was between 120 and 140°C. After being kept at 190°C for 30 minutes, it was naturally cooled to room temperature and filtered. The obtained polyimide resin powder was washed with 300 g of 2-(2-methoxyethoxy)ethanol and 300 g of methanol, filtered, and dried in a dryer at 180° C. for 10 hours to obtain 317 g of a powder of crystalline thermoplastic polyimide resin 1 (hereinafter also simply referred to as “polyimide resin 1”).

[0248] The IR spectrum of polyimide resin 1 was measured and the results showed that ν(C=O) was 1768, 1697 (cm -1 ) The characteristic absorption of the imide ring was confirmed. The logarithmic viscosity was 1.30 dL / g, Tm was 323°C, Tg was 184°C, Tc was 266°C, the heat of fusion was 21.0 mJ / mg, the heat of crystallization was 20.3 mJ / mg, the half crystallization time was less than 20 seconds, and the Mw was 55,000.

[0249] Production Example 2 (Production of Polyimide Resin 2)

[0250] In a 2L separable flask equipped with a Dean-Stark trap, a Liebig condenser, a thermocouple, and four paddles, 769 g of 2-(2-methoxyethoxy)ethanol (manufactured by Nippon Emulsifier Co., Ltd.) and 174.50 g (0.80 mol) of pyromellitic dianhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.) were introduced, and nitrogen was flowed, followed by stirring at 150 rpm to obtain a uniform suspension solution. On the other hand, 34.14 g (0.24 mol) of 1,3-bis(aminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., cis / trans ratio = 7 / 3) and 80.79 g (0.56 mol) of 1,8-octamethylenediamine (manufactured by Kanto Chemical Co., Ltd.) were dissolved in 250 g of 2-(2-methoxyethoxy)ethanol in a 500 mL beaker to prepare a mixed diamine solution. The mixed diamine solution was slowly added using a plunger pump. Heat was released by the addition, but the internal temperature was adjusted to fall within the range of 40 to 80°C. A nitrogen flow state was formed during the addition of the mixed diamine solution, and the stirring blade speed was set to 200 rpm. After the addition was completed, 10 g of 2-(2-methoxyethoxy)ethanol and 1.027 g (0.008 mol) of n-octylamine (manufactured by Kanto Chemical Co., Ltd.) as an end-capping agent were added and further stirred. At this stage, a light yellow polyamic acid solution was obtained. Next, after the stirring speed was set to 250 rpm, the polyamic acid solution in the 2L detachable flask was heated to 185°C. During the gradual heating process, the precipitation of polyimide resin powder and dehydration accompanied by imidization were confirmed when the liquid temperature was between 120 and 140°C. After being kept at 185°C for 30 minutes, it was naturally cooled to room temperature and filtered. The obtained polyimide resin powder was washed with 600 g of methanol, filtered, and then dried in a dryer at 185° C. for 10 hours to obtain 256 g of a powder of a crystalline thermoplastic polyimide resin 2 (hereinafter, also simply referred to as “polyimide resin 2”).

[0251] The polyimide resin 2 had a Tm of 330° C., a Tg of 179° C., a Tc of 278° C., a heat of fusion of 34 mJ / mg, a heat of crystallization of 32 mJ / mg, and a Mw of 37,000.

[0252] Production Example 3 (Production of Polyimide Resin 3)

[0253] In a 2L separable flask equipped with a Dean-Stark trap, a Liebig condenser, a thermocouple, and four paddles, 769 g of 2-(2-methoxyethoxy)ethanol (manufactured by Nippon Emulsifier Co., Ltd.) and 174.50 g (0.80 mol) of pyromellitic dianhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.) were introduced, and nitrogen was flowed, followed by stirring at 150 rpm to obtain a uniform suspension solution. On the other hand, 22.76 g (0.16 mol) of 1,3-bis(aminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., cis / trans ratio = 7 / 3) and 92.33 g (0.64 mol) of 1,8-octamethylenediamine (manufactured by Kanto Chemical Co., Ltd.) were dissolved in 250 g of 2-(2-methoxyethoxy)ethanol in a 500 mL beaker to prepare a mixed diamine solution. The mixed diamine solution was slowly added using a plunger pump. Heat was released by the addition, but the internal temperature was adjusted to fall within the range of 40 to 80°C. A nitrogen flow state was formed during the addition of the mixed diamine solution, and the stirring blade speed was set to 250 rpm. After the addition was completed, 10 g of 2-(2-methoxyethoxy)ethanol and 1.027 g (0.008 mol) of n-octylamine (manufactured by Kanto Chemical Co., Ltd.) as an end-capping agent were added and further stirred. At this stage, a light yellow polyamic acid solution was obtained. Next, after the stirring speed was set to 200 rpm, the polyamic acid solution in the 2L detachable flask was heated to 185°C. During the gradual heating process, the precipitation of polyimide resin powder and dehydration accompanied by imidization were confirmed when the liquid temperature was between 120 and 140°C. After being kept at 185°C for 30 minutes, it was naturally cooled to room temperature and filtered. The obtained polyimide resin powder was washed with 600 g of methanol, filtered, and then dried in a dryer at 185° C. for 10 hours to obtain 256 g of a powder of crystalline thermoplastic polyimide resin 3 (hereinafter, also simply referred to as “polyimide resin 3”).

[0254] The IR spectrum of the polyimide resin 3 was measured, and the results showed that Tm was 344° C., Tg was 166° C., Tc was 299° C., heat of fusion was 40 mJ / mg, heat of crystallization was 35 mJ / mg, and Mw was 36,000.

[0255] Production Example 4 (Production of Polyimide Resin 4)

[0256] Into a 2L detachable flask equipped with a Dean-Stark trap, a Liebig condenser, a thermocouple, and four paddles, 650 g of 2-(2-methoxyethoxy)ethanol (manufactured by Nippon Emulsifier Co., Ltd.) and 257.75 g (1.180 mol) of pyromellitic dianhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.) were introduced, and after nitrogen flow was formed, the mixture was stirred at 150 rpm to form a uniform suspension solution. On the other hand, 83.96 g (0.5902 mol) of 1,3-bis(aminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., cis / trans ratio = 7 / 3), 54.86 g (0.4722 mol) of 1,6-hexamethylenediamine (manufactured by FUJIFILM WakoChemicals Corporation), and 23.64 g (0.1180 mol) of 4,4'-diaminodiphenyl ether (manufactured by Wakayama Seika Industries, Ltd.) were dissolved in 250 g of 2-(2-methoxyethoxy)ethanol in a 500 mL beaker to prepare a mixed diamine solution. The mixed diamine solution was slowly added using a plunger pump. Although heat was generated by the dropwise addition, the internal temperature was adjusted to fall within the range of 40 to 80°C. During the dropwise addition of the mixed diamine solution, a nitrogen flow state was formed throughout, and the stirring blade rotation speed was set to 250 rpm. After the addition is completed, 100 g of 2-(2-methoxyethoxy)ethanol and 2.270 g (0.0176 mol) of n-octylamine (manufactured by Kanto Chemical Co., Ltd.) as an end-capping agent are added and further stirred. At this stage, a yellow transparent uniform polyamic acid solution is obtained. Then, after the stirring speed is set to 200 rpm, the polyamic acid solution in the 2L detachable flask is heated to 190 ° C. In the process of gradually heating up, the precipitation of polyimide resin powder and dehydration accompanied by imidization are confirmed when the liquid temperature is between 130 and 150 ° C. After keeping at 190 ° C for 30 minutes, it is naturally cooled to room temperature and filtered. The obtained polyimide resin powder is washed and filtered with 300 g of 2-(2-methoxyethoxy)ethanol and 300 g of methanol, and then dried at 190 ° C for 10 hours in a dryer to obtain 360 g of polyimide resin 4 powder.

[0257] The IR spectrum of polyimide resin 4 was measured and the results showed that ν(C=O) was 1771, 1699 (cm -1 ) The characteristic absorption of the imide ring was confirmed. The logarithmic viscosity was 0.63 dL / g, Tm was 337°C, Tg was 233°C, Tc was 283°C, the heat of fusion was 20 mJ / mg, the heat of crystallization was 24 mJ / mg, the half crystallization time was less than 20 seconds, and the Mw was 30,000.

[0258] The compositions and evaluation results of the polyimide resins (A) obtained in Production Examples 1 to 4 are shown in Table 1. In addition, the mol % of the tetracarboxylic acid component and the diamine component in Table 1 are values ​​calculated from the input amounts of the components when producing the polyimide resin.

[0259] [Table 1]

[0260]

[0261] The abbreviations in Table 1 are as follows.

[0262] PMDA; pyromellitic dianhydride

[0263] 1,3-BAC; 1,3-bis(aminomethyl)cyclohexane

[0264] OMDA; 1,8-octamethylenediamine

[0265] ·HMDA; 1,6-hexamethylenediamine

[0266] ·ODA; 4,4'-diaminodiphenyl ether

[0267] ·n-OcA; n-octylamine

[0268] ·BzA; benzylamine

[0269] Example 1 (Preparation of thermoplastic resin composition, molded article and evaluation of thermal properties)

[0270] The powder of the polyimide resin 1 obtained in Production Example 1 was mixed with a polyetherketoneketone resin ("7002" manufactured by ARKEMA, T / I ratio: 70 / 30, Tm B =330°C, Tg=157°C) pellets were dry-blended in the proportions shown in Table 2, and then melt-blended and extruded using a co-rotating twin-screw kneading extruder (Parker Corporation "HK-25D", screw diameter 25 mmΦ, L / D=41) at a barrel temperature of 370°C and a screw speed of 150 rpm. The filaments extruded from the extruder were air-cooled and pelletized using a pelletizer (HOSHIPlastic Co., Ltd. "Fan-cutter FC-Mini-4 / N"). The obtained pellets were dried at 150°C for 12 hours and then used for injection molding.

[0271] Injection molding was performed using an injection molding machine ("ROBOSHOTα-S130iA" manufactured by FANUC Corporation) at a barrel temperature of 360°C, a mold temperature of 200°C, and a molding cycle of 207 seconds to produce an injection molded body of a predetermined shape used in the above evaluation (HDT measurement).

[0272] The obtained pellets or injection molded bodies were used to perform various evaluations by the above-mentioned methods.

[0273] Example 2

[0274] Pellets and injection molded bodies were prepared and various evaluations were performed in the same manner as in Example 1 except that the powder of polyimide resin 1 obtained in Production Example 1 and the pellets of polyetherketoneketone resin were used in the ratio shown in Table 2 and injection molding was performed at a molding cycle of 244 seconds. The results are shown in Table 2.

[0275] Example 3

[0276] Pellets and injection molded bodies were prepared and various evaluations were performed in the same manner as in Example 1 except that the powder of polyimide resin 1 obtained in Production Example 1 and the pellets of polyetherketoneketone resin were used in the ratio shown in Table 2 and injection molding was performed at a molding cycle of 224 seconds. The results are shown in Table 2.

[0277] Example 4

[0278] Pellets and injection molded bodies were prepared and various evaluations were performed in the same manner as in Example 1 except that the powder of polyimide resin 1 obtained in Production Example 1 and the pellets of polyetherketoneketone resin were used in the ratio shown in Table 2 and injection molding was performed at a molding cycle of 374 seconds. The results are shown in Table 2.

[0279] Comparative Example 1

[0280] The powder of the polyimide resin 1 obtained in Preparation Example 1 was melt-kneaded and extruded using a LABO PLASTOMILL (manufactured by Toyo Seiki Seisaku-sho, Ltd.) at a barrel temperature of 360° C. and a screw speed of 150 rpm. The strands extruded from the extruder were air-cooled and pelletized using a pelletizer (“Fan-cutter FC-Mini-4 / N” manufactured by HOSHI Plastic Co., Ltd.). The pellets were dried at 150° C. for 12 hours and then used for injection molding.

[0281] Injection molding was performed using an injection molding machine ("ROBOSHOTα-S30iA" manufactured by FANUC Corporation) at a barrel temperature of 350°C, a mold temperature of 200°C, and a molding cycle of 50 seconds to produce an injection molded body of a predetermined shape used in the above evaluation (HDT measurement).

[0282] The obtained pellets or injection molded bodies were used to perform various evaluations by the above-mentioned methods.

[0283] Comparative Example 2

[0284] The pellets of the polyetherketoneketone resin ("7002" manufactured by ARKEMA) were dried at 160°C for 6 hours and then used for injection molding.

[0285] An injection molding machine ("ROBOSHOTα-S130iA" manufactured by FANUC Corporation) was used to perform injection molding at a barrel temperature of 360°C, a mold temperature of 200°C, and a molding cycle of 404 seconds to produce an injection molded body of a predetermined shape used in the above evaluation (HDT measurement).

[0286] The obtained pellets or injection molded bodies were used to perform various evaluations by the above-mentioned methods.

[0287] Comparative Example 3

[0288] In Example 4, a polyetheretherketone resin (B') (PEEK, "PEEK90G" manufactured by VICTREX, Tm B The pellets and injection molded products were prepared in the same manner as in Example 4, and various evaluations were performed. The results are shown in Table 2.

[0289] Comparative Example 4

[0290] The polyetheretherketone resin (PEEK 90G manufactured by VICTREX) was melt-kneaded and extruded using LABO PLASTOMILL (manufactured by Toyo Seiki Seisakusho, Ltd.) at a barrel temperature of 350°C and a screw speed of 150 rpm. The strands extruded from the extruder were air-cooled and pelletized using a pelletizer (Fan-cutter FC-Mini-4 / N manufactured by HOSHI Plastic Co., Ltd.). The pellets were dried at 160°C for 6 hours and then used for injection molding.

[0291] An injection molding machine ("ROBOSHOTα-S30iA" manufactured by FANUC Corporation) was used to perform injection molding at a barrel temperature of 350°C, a mold temperature of 195°C, and a molding cycle of 60 seconds to produce an injection molded body of a predetermined shape used in the above evaluation (HDT measurement).

[0292] The obtained pellets or injection molded bodies were used to perform various evaluations by the above-mentioned methods.

[0293] Comparative Examples 5 to 7

[0294] In Comparative Example 1, except that the powder of the polyimide resin described in Table 2 was used instead of the powder of the polyimide resin 1, pellets were prepared in the same manner as in Comparative Example 1 and various evaluations were performed.

[0295] Embodiments 5 to 7

[0296] In Example 4, except having used the powder of the polyimide resin described in Table 2 instead of the powder of the polyimide resin 1, it carried out similarly to Example 4 to prepare pellets and perform various evaluations.

[0297] [Table 2]

[0298]

[0299] The details of each component shown in Table 2 are as follows.

[0300] <Crystalline thermoplastic polyimide resin (A)>

[0301] Polyimide resins 1 to 4: Crystalline thermoplastic polyimide resins 1 to 4 obtained in Production Examples 1 to 4

[0302] <Polyetherketoneketone resin (B)>

[0303] ·ARKEMA "7002", T / I ratio: 70 / 30, Tm B =330℃、Tg=157℃

[0304] <Polyetheretherketone resin (B')>

[0305] ·PEEK 90G made by VICTREX, Tm B =342℃、Tg=154℃

[0306] As shown in Table 2, the minimum crystallization temperature Tc of the thermoplastic resin composition of this embodiment (Examples 1 to 7) is MIN The crystallization temperature Hc of the thermoplastic resin composition of the present example is lower than the crystallization temperature Tc of the component (A) or the component (B) alone as the raw material resin. Furthermore, the crystallization heat Hc of the thermoplastic resin composition of the present example is 10 mJ / mg or more, and sufficient crystallinity is maintained.

[0307] In addition, the (Tm-Tc MIN ) becomes higher than the value of the component (A) or the component (B) alone as the raw material resin, and it is considered that it has more suitable physical properties for thermoforming.

[0308] Furthermore, the morphology of the pellets and injection-molded article obtained in Example 3 was confirmed by the following method.

[0309] Using an ultra-thin slicer ("EMUC7" manufactured by Leica Microsystems), Figure 1As shown, the pellets obtained in Example 3 were cut along a direction perpendicular to the flow direction (MD) of the pellets (ie, in a manner such that a TD cross section appears) to prepare ultrathin sections. Figure 1 In the figure, 1 is a pellet and 2 is an ultrathin slice.

[0310] The slice was stained in the gas phase of ruthenium tetroxide for 30 minutes, and then observed using a field emission scanning transmission electron microscope (FE-STEM, "GeminiSEM500" manufactured by ZEISS) at an accelerating voltage of 30 kV and an observation magnification of 30,000 times using a STEM detector ( Figure 2 ).

[0311] In addition, the injection molded body obtained in Example 3 was cut with a diamond wheel saw (SOUTHBAYTECHNOLOGY "MODEL650") along the direction orthogonal to the flow direction (MD) of the test part of the multifunctional test piece of the injection molded body (i.e., in the form of a TD cross section), and the central part of the test part was cut out. From the vicinity of the center of the cut cross section, ultrathin sections were made using an ultrathin slicer according to the same steps as the pellets. After the sections were stained in the gas phase of ruthenium tetroxide for 30 minutes, they were observed using a field emission scanning transmission electron microscope (FE-STEM, ZEISS "GeminiSEM500") at an accelerating voltage of 30 kV and an observation magnification of 30,000 times ( Figure 3 ).

[0312] according to Figure 2 and Figure 3 It can be seen that in the pellets and injection molded bodies obtained in Example 3, the crystalline thermoplastic polyimide resin (A) and the polyetherketoneketone resin (B) form a sheet-like microphase separation structure.

[0313] Example 8 (Production and Evaluation of Film, and Evaluation of Adhesion between the Film and Copper Foil)

[0314] <Film production>

[0315] The pellets of the thermoplastic resin composition obtained in Example 3 were dried at 150° C. for 10 hours and then introduced into a 150 mm wide T-die. The single screw extruder was used to perform melt kneading at a resin temperature of 350 to 360° C. The melt kneaded thermoplastic resin composition was continuously extruded from the T die of the single screw extruder, and then cooled on a metal roll serving as a cooling roll at 140° C. to obtain a film having a thickness of 50 μm.

[0316] Here, The temperature of the single screw extruder was set at 335-340°C, and the temperature of the T die was set at 335°C.

[0317] <Total light transmittance>

[0318] The total light transmittance (%) of the film was measured in accordance with JIS K7361-1:1997 using a color / turbidity simultaneous measuring device ("COH400" manufactured by Nippon Denshoku Industries Co., Ltd.).

[0319] <Haze>

[0320] The haze (%) of the film was measured in accordance with JIS K7136:2000 using a color / turbidity simultaneous measuring device ("COH400" manufactured by Nippon Denshoku Industries Co., Ltd.).

[0321] <YI>

[0322] The YI value of the film was measured in accordance with JIS K7373:2006 using a color / turbidity simultaneous measuring device ("COH400" manufactured by Nippon Denshoku Industries Co., Ltd.).

[0323] <Color tone (Lab)>

[0324] The L, a, and b values ​​of the film were measured by a reflection method using a colorimeter (“ZE2000” manufactured by Nippon Denshoku Industries, Ltd.) in accordance with JIS Z8781-4:2013.

[0325] <Dielectric constant, dielectric loss tangent>

[0326] The dielectric constant and dielectric loss tangent of the film were measured as follows: The dielectric constant and dielectric loss tangent were measured at a temperature of 23°C, a humidity of 50%, and a measurement frequency of 10 GHz using a "PNA-L network analyzer N5230A" manufactured by Agilent Technologies, Inc. and a cavity resonator "CP531" manufactured by Kanto Electronics Application Development Co., Ltd., in accordance with IEC 62810, according to the cavity resonator perturbation method. The measured value was set as an average value of n = 2. The film was dried in a desiccator and then immediately used for measurement.

[0327] <Adhesion between films>

[0328] Prepare the 10 cm × 10 cm films 3a and 3b made by the above method. Figure 4 As shown in (a), two films 3a and 3b are placed so that the two films overlap by 1 cm ( Figure 4 d=1 cm in (a). Another piece of release paper was placed on it and heat-sealed using a thermal tilt tester (manufactured by Toyo Seiki Seisaku-sho, Ltd., heater: upper side). The heat-sealing conditions were as follows: 250°C, 0.4 MPa (gauge pressure) for 60 seconds.

[0329] After heat sealing, remove the release paper and Figure 4 The film shown in (a) was cut in the MD direction to prepare a strip test piece with a width of 1 cm ( Figure 4 (b)). Figure 4 The bonding area between the films 3a' and 3b' in (b) is 1 cm 2 .

[0330] Next, hold the obtained test piece by one short side, as Figure 5 As shown, when the film is hung so that the long side is parallel to the direction of gravity, if the lower film does not fall within 30 seconds, it is judged to have adhesion.

[0331] <Adhesion between film and copper foil>

[0332] A 10 cm x 10 cm film 3a and a 10 cm x 10 cm x 12 μm thick copper foil 4 (rolled copper foil, "BHM-102F-HA-V2" produced by JX Metal Co., Ltd.) were prepared. Figure 6 As shown in (a), copper foil 4 and film 3a are placed in this order, and the copper foil 4 and film 3a are overlapped by 1 cm ( Figure 6 d=1 cm in (a). Another piece of release paper was placed on it and heat-sealed using a thermal tilt tester (manufactured by Toyo Seiki Seisaku-sho, Ltd., heater: upper side). The heat-sealing conditions were as follows: 250°C, 0.4 MPa (gauge pressure) for 60 seconds.

[0333] After heat sealing, remove the release paper and Figure 6 The film shown in (a) was cut in the MD direction to prepare a strip test piece with a width of 1 cm ( Figure 6 (b)). Figure 6 The bonding area between the film 3a' and the copper foil 4' in (b) is 1 cm 2 .

[0334] Next, the short side of the obtained test piece film 3a' is held, as shown in FIG. Figure 7 As shown, when the copper foil 4' on the lower side is hung so that the long side is parallel to the gravity direction, it is judged that there is adhesion if the copper foil 4' on the lower side does not fall within 30 seconds.

[0335] <Tensile bond strength>

[0336] The test piece was prepared in the same manner as the above-mentioned "adhesion to copper foil" evaluation and used for evaluation. The test piece was set on the clamping tool of a universal testing machine ("Strograph VG" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.) so that the upper side became a film and the lower side became a copper foil, and the long side was parallel to the gravity direction ( Figure 7According to JIS K 6849-1994, a tensile shear test was conducted at a temperature of 23°C, a test range of 200 N, and a test speed of 5 mm / min to determine the tensile bond strength (N / cm 2 ).

[0337] Example 9, Comparative Examples 8-10

[0338] Films were produced and evaluated in the same manner as in Example 8 except that the thermoplastic resin composition used for producing the film was changed to the thermoplastic resin or thermoplastic resin composition described in Table 3. The results are shown in Table 3.

[0339] [Table 3]

[0340] Table 3

[0341]

[0342] The details of each component shown in Table 3 are as follows.

[0343] <Crystalline thermoplastic polyimide resin (A)>

[0344] Polyimide resin 1: Crystalline thermoplastic polyimide resin 1 obtained in Production Example 1

[0345] <Polyetherketoneketone resin (B)>

[0346] ·ARKEMA "7002", T / I ratio: 70 / 30, Tm B =330℃、Tg=157℃

[0347] <Polyetheretherketone resin (B')>

[0348] ·PEEK 90G made by VICTREX, Tm B =342℃、Tg=154℃

[0349] According to Table 3, the film formed from the thermoplastic resin composition of the present invention has no significant decrease in total light transmittance or extreme increase in haze, YI, etc., compared with a film formed from one thermoplastic resin, and has transparency. In addition, it has a low dielectric constant and a low dielectric loss tangent, and can also ensure adhesion between the films and between the film and the copper foil.

[0350] Note that, as shown in Comparative Example 10, the adhesion between the PEEK film and the copper foil is low.

[0351] Industrial Applicability

[0352] The thermoplastic resin composition of the present invention has heat resistance and crystallinity, the rise of crystallization temperature is suppressed, the thermoformability is good, and it is not easy to produce a decrease in adhesion and shrinkage during three-dimensional modeling, so it is suitable as a molding material for a 3D printer, for example. In addition, the thermoplastic resin composition of the present invention has good adhesion to the adherend due to the effect of reducing the crystallization temperature, and has high heat resistance, so it is also suitable for application in metal foil laminates such as bonding sheets and copper-clad laminates.

[0353] Description of Reference Numerals

[0354] 1 pellet

[0355] 2 Ultrathin sections

[0356] 3a, 3b, 3a', 3b' films

[0357] 4. 4' copper foil.

Claims

1. A thermoplastic resin composition comprising a crystalline thermoplastic polyimide resin (A) and a polyetherketoneketone resin (B), wherein the crystalline thermoplastic polyimide resin (A) comprises a repeating structural unit represented by the following formula (1) and a repeating structural unit represented by the following formula (2), wherein the content ratio of the repeating structural unit of the formula (1) to the total of the repeating structural unit of the formula (1) and the repeating structural unit of the formula (2) is 15 to 70 mol%. The melting point Tm of the component (A) A The melting point Tm of the component (B) B The absolute value of the difference |Tm A -Tm B |0~40℃, R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure, R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms, and X1 and X2 are each independently a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.

2. The thermoplastic resin composition according to claim 1, wherein The melting point Tm of the component (A) A and the melting point Tm of the component (B) B The temperature ranges from 270 to 360°C.

3. The thermoplastic resin composition according to claim 1 or 2, wherein The mass ratio of the component (A) to the component (B) in the thermoplastic resin composition is 1 / 99 to 80 / 20.

4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein The total content of the component (A) and the component (B) in the thermoplastic resin composition is 50% by mass or more.

5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein The thermoplastic resin composition has a crystallization heat of 10 mJ / mg or more.

6. The thermoplastic resin composition according to any one of claims 1 to 5, wherein The thermoplastic resin composition has a melting point Tm, and a difference between the melting point Tm and a crystallization temperature Tc of the thermoplastic resin composition, that is, Tm-Tc, is 65° C. or more.

7. The thermoplastic resin composition according to claim 6, wherein The Tm-Tc is 80°C or higher.

8. The thermoplastic resin composition according to any one of claims 1 to 7, wherein The thermoplastic resin composition has a lamellar microphase separation structure. 9 . The thermoplastic resin composition according to claim 1 , further comprising a filler. 10 . A molded product comprising the thermoplastic resin composition according to claim 1 . 11 . A metal foil laminate comprising: a layer formed of the molded article according to claim 10 ; and a layer formed of a metal foil. 12 . A joining sheet comprising the thermoplastic resin composition according to claim 1 . 13 . A filament comprising the thermoplastic resin composition according to claim 1 .

14. A three-dimensional modeling material comprising the thermoplastic resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for manufacturing laminate for flexible printed wiring board, laminate for flexible printed wiring board and flexible printed wiring board

    JP2010221694A

  • Crystalline thermoplastic polyimide resin

    WO2013118704A1

  • Polyimide resin

    WO2016147996A1

  • Resin molding

    WO2019220969A1